2019
DOI: 10.1039/c9ta04369a
|View full text |Cite
|
Sign up to set email alerts
|

High-performance supercapacitor energy storage using a carbon material derived from lignin by bacterial activation before carbonization

Abstract: A novel green bacterial activation method for the synthesis of a lignin derived carbon material with excellent electrochemical performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…Biomass gradually converts into biocarbon during pyrolysis by thermochemical decomposition at high temperatures in the absence of oxygen 125 . Note that high‐temperature pyrolysis includes conventional pyrolysis, 126,127 microwave pyrolysis, 108,128 solar pyrolysis, 129,130 plasma pyrolysis, 131,132 and catalytic pyrolysis 133,134 …”
Section: Preparation Of Bdcsmentioning
confidence: 99%
“…Biomass gradually converts into biocarbon during pyrolysis by thermochemical decomposition at high temperatures in the absence of oxygen 125 . Note that high‐temperature pyrolysis includes conventional pyrolysis, 126,127 microwave pyrolysis, 108,128 solar pyrolysis, 129,130 plasma pyrolysis, 131,132 and catalytic pyrolysis 133,134 …”
Section: Preparation Of Bdcsmentioning
confidence: 99%
“…The nitrogen adsorption/desorption isotherm and the corresponding pore size distribution curves calculated by the density functional theory (DFT) method are shown in Figure 3a,b, respectively. As shown in Figure 3a, all samples exhibit type-IV isotherm curves with two steep uptakes (P/P0 < 0.01, P/P0 > 0.96) and an obvious hysteresis loop (0.4 < P/P0 <0.96), suggesting a hierarchically skeletal structure and coexistence of micropores, mesopores, and macropores [41]. The micro-, meso-, and macropores are considered to act as an extra source of faradaic pseudocapacitance, a highway for ion transport, and a buffering reservoir for electrolyte, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…While specific capacitance by some researches is high (e. g., over 200 F g −1 ), the energy (E ) and power (P) densities are not as impressive (Table 4). For instance, Zhang et al (2019) reported specific capacitance at 289 F g −1 at 1 A g −1 , while E and P were 66.2 Wh kg −1 and 0.31 W kg −1 , respectively. The lower E and P could be attributed to their operating voltage window of 2.5 V, which was narrower than that used in this research work (3.5 V).…”
Section: Edlcsamplesmentioning
confidence: 99%